إصلاح عيوب الأنابيب الفولاذية باستخدام مادة الايبوكسي - هترة علي; منصور رامي; الوزة لورا (Latakia University Journal -Engineering Sciences Series, 2017)
يتناول هذا البحث كيفية القيام بعملية إصلاح عيوب الأنابيب الفولاذية بطريقة سهلة وبسيطة. في البداية تنظف المنطقة المحيطة بالعيب ثم تطبق مادة الايبوكسي فوق العيب بعد مزج الريزين مع المقسي بشكل جيد. تعتمد أبعاد طبقة الايبوكسي على أبعاد العيب الموجود في الأنبوب. بعدها تترك العينة فترة من الزمن لتتحقق عملية التصلب. استخدمت عدة أنواع من الايبوكسي لتحضير مجموعة من العينات التي تم اختبارها على جهاز الضغط لتقييم فعالية هذه الطريقة في الإصلاح ومعرفة قيم الضغط الذي يمكن أن تتحمله طبقة الايبوكسي. تمت معالجة أنبوب يحوي ثلاثة ثقوب متساوية الأقطار باستخدام ALTECO QUICK EPOXY STEEL وسجل مقياس الضغط قيماً وصلت حتى 18 بار. رسم المنحني الممثل للعلاقة بين الضغط الذي تتحمله طبقة الايبوكسي ومساحتها السطحية، ووجد أن العامل الأكثر تأثيراً في عملية الإصلاح هو طريقة تحضير العينة وسماكة طبقة الايبوكسي. This research carries how to do steel pipelines defects repair process by a simple and easy way. At first the region that surrounds the defect is cleaned then the epoxy material is put over the defect after mixing the resin with the hardener well. Epoxy layer dimensions depend on the defect dimensions that exists in the pipe. After that, the specimen is released for a period of time to obtain the setting process. Several types of epoxy were used for preparing series of specimens, which were tested on the pressure set up to estimate the efficiency of this way in the repair, and knowing the pressure values that epoxy layer can carry. A pipe of three holes their radius are equal, was treated by using ALTECO QUICK EPOXY STEEL and the pressure gauge recorded many values that reached 18 bar. The curve, that represents the relationship between the pressure which the epoxy layer carried and its surface area, was drawn. It is found that the most effect factor in the repair process is the specimen preparing and the thickness of the epoxy layer.